Growth of AlN Crystal Using Reactive Sputtering Method With Variation of Nitrogen Gas Pressure and Substrate Temperature - dianita warda dani (BATAN, 2017)
Today’s semi-conductor technology continues to develop, both in terms of material discovery, manufacturing technique, as well as implementation and the development. In this research, the researcher will utilize the AlN synthesis with a reactive sputtering method on the substrate SiO2 that has done with variation substrate temperature of (200, 250, 300oC), and the nitrogen gas pressure of 10, 15 and 20 mBar. This study successfully synthesize nanomaterial AlN with a hexagonal crystal system and shows the wurtzite phase is formed. While morphology AlN formed composed of particles - spherical shaped particles. From this research it is known that raising the temperature of the substrate produces more uniform morphology and homogeneous, the surface roughness is formed from 15,4 to 84 nm and obtained the crystal size is 64-87 nm. While the addition of nitrogen gas pressure causes the better crystallinity. The research obtained AlN with Optical Transversal wave type at a wavenumber of 600-670 cm-1. While the growth of AlN crystal growth of AlN is best obtained on the parameters of the substrate temperature 290 °C and nitrogen gas pressure of 20 mbar.